Investigation of low current gas tungsten arc welding using split anode calorimetry - Egerland, Stephan; Colegrove, Paul A.; Williams, Stewart W. (Taylor and Francis, 2016)
Most previous split anode calorimetry research has applied high weld currents which exhibit pseudo Gaussian distributions of arc current and power density. In this paper we investigate low current arcs and show that both the current and power distributions have minima in the centre – varying significantly from the expected Gaussian profile. This was postulated due to the formation of the arc with the copper anode and the tungsten cathode. Furthermore, a number of parameters were varied including the step size between measurements, anode thickness and anode surface condition as well as cathode type and tip geometry. The step size between measurements significantly influenced the distribution profile and the anode thickness needed to be above 7 mm to obtain consistent results.
Keywords: Split anode; Weld calorimetry; GTAW; Arc energy; Current density; Power density; Electrode